(untitled) (Mustansiria Dental Journal, 2018)
The present study was performed to evaluate the effectiveness of newly designed motor-driven fiberglass burs in root planing and compare it to manual instrumentation using universal curette. Twelve patients complaining from periodontitis with deep periodontal pockets were involved in this study. A total number of 139 pocket sites received root planing by motor-driven fiberglass burs and 131 pocket sites were planed manually by curette. The root planing procedure was opened type; it was performed by modified widman flap operation. The clinical parameters that were used in this study are (plaque index, bleeding on probing, probing pocket depth and relative attachment level). They were recorded in 4 periodic visits 2 of them before treatment and 2 after treatment to assess the improvement and to make a comparison between the two methods of treatment. The results revealed that there was a significant improvement in all of the clinical parameters after treatment with fiberglass burs. Also the results showed that that there was no significant difference between the improvement that was implemented by the two methods of treatment.